Microbiological etiology and management approach of febrile neutropenia - Alshaer, Omar Rezk; Binobaid, Abdullah Obaid; Alharthi, Yousef Hussain; Alrashdi, Abdulaziz Ashwa; Alrashed, Muath Saleh; Alluhayyan, Fahad Barikan; Alghasham, Khuzama Abdullah; Alqifari, Abdulrahman Abdullah; Alkhamis, Riam Saleh; Alhajji, Maryiah Abdulaziz; Almutairi, Noura Talal (International Journal Of Community Medicine And Public Health, 2021)
Many etiologies have been proposed to predispose neutropenic fever, and infections have been reported in less than one-third of the reported cases. However, etiologies might have a significant impact on the prognostic, and can even lead to mortality. In this literature review, the aim to discuss the different microbiological etiologies of neutropenic fever, and the management approaches of such conditions, including the proper assessment and evaluation of patients. Additionally, the goal of this literature review to discuss the appropriate treatment and prophylaxis measures based on the assessment results. Many bacterial pathogens could be isolated from patients suffering from neutropenic fever, including both the gram-positive and negative organisms, such as pseudomonas aeruginosa, E. coli, Klebsiella spp, actinobacteria spp, in addition to many other bacteria such as staph. Nevertheless, Aureus was commonly isolated from the infected patients, and it has been reported with increased morbidity and mortality rates. Assessment of the severity of the condition and identification of the microbiological activity can significantly lead to enhance management of the infected patients. Detailed information about the etiology and management are provided within the main text of this study. Further efforts are needed to increase awareness related to the hazards of the inadequate and incomplete assessments of patients with neutropenic fever, which might lead to delayed or inadequate management and worsened prognosis.